2021
DOI: 10.3389/fneur.2020.611875
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Ruptured Wide-Necked Anterior Communicating Artery Aneurysms Using a Low-Profile Visualized Intraluminal Support (LVIS) Device

Abstract: Objective: To evaluate the safety and efficacy of low-profile visualized intraluminal support (LVIS) stent-assisted coiling for the treatment of ruptured wide-necked anterior communicating artery (ACoA) aneurysms.Methods: The clinical and angiographic data of 31 acutely ruptured wide-necked ACoA aneurysms treated with LVIS stent-assisted coiling between January 2014 and December 2018 were retrospectively reviewed.Results: All stents were successfully deployed. The immediate angiographic results were modified R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Moreover, for aneurysms located in small arteries with small and tortuous parent artery, the procedure could lead to a higher incidence of thromboembolic events. 5 Xue et al 7 reported 31 acutely ruptured wide-necked anterior communicating artery aneurysms treated with LVIS stent. Intraoperative thrombosis and postoperative aneurysmal rebleeding occurred in 1 case each (3.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for aneurysms located in small arteries with small and tortuous parent artery, the procedure could lead to a higher incidence of thromboembolic events. 5 Xue et al 7 reported 31 acutely ruptured wide-necked anterior communicating artery aneurysms treated with LVIS stent. Intraoperative thrombosis and postoperative aneurysmal rebleeding occurred in 1 case each (3.2%).…”
Section: Discussionmentioning
confidence: 99%
“…After deployment of the first coil, an initial bolus of 50 U/kg heparin was given, and the activated clotting time was maintained at two times the normal range. For wide-neck aneurysms, ( 14 ) coiling with a stent or a balloon was performed by interventionalists with 20 years of experience at each center. During the procedure of stent-assisted coiling, patients would be allocated 300 mg clopidogrel and 300 mg aspirin.…”
Section: Methodsmentioning
confidence: 99%